ANALISIS KINERJA KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PROSES PRODUKSI SAUS DENGAN METODE FAULT TREE ANALYSIS - Arif Nuryono; Hibarkah Kurnia; Erwin Barita Tambunan; Tri Ngudi Wiyatno (Jurnal Ilmiah Teknik Industri, 2023)
The production process for making sauces requires a performance appraisal so that the results are effective and efficient. In production, performance problems sometimes occur, such as low productivity and accidents. The relationship between employee performance, such as work safety greatly affects work productivity. The purpose of this study was to analyze the performance of K3 which includes the Frequency Rate (FR), Severity Rate (SR), and T-Safety Value (NTS) so that it will produce how big the relationship is between the accident rate and work productivity. This study uses the Fault Tree Analysis (FTA) method where to build an FTA flowchart, it is necessary to identify work accident data, build a safety tree, measure work productivity, and draw conclusions. This research has produced several analyzes using FTA where the FR, SR, and NTS levels can already be known. The results of measuring the FR value show a decrease in the frequency of disability injuries and the severity of work accidents from year to year, there is a decrease from year to year. This research has also succeeded in increasing employee work productivity due to the low value of the FR and SR levels each year. If linked to NTS, every year the relationship between work safety and productivity will improve. So from the results of this analysis, there is a relationship between the frequency of work accidents and the level of work productivity that occurs in the production process.